Diamond as Insulation for Conductive Diamond—A Spotted Pattern Design for Miniaturized Disinfection Devices - Zulla, Manuel; Vierheilig, Vera; Koch, Maximilian; Burkovski, Andreas; Karl, Matthias; Rosiwal, Stefan (C – Journal of Carbon Research, 2023)
Boron-doped diamond (BDD) electrodes are well known for the in situ production of strong oxidants. These antimicrobial agents are produced directly from water without the need of storage or stabilization. An in situ production of reactive oxygen species (ROS) used as antimicrobial agents has also been used in recently developed medical applications. Although BDD electrodes also produce ROS during water electrolysis, only a few medical applications have appeared in the literature to date. This is probably due to the difficulties in the miniaturization of BDD electrodes, while maintaining a stable and efficient electrolytic process in order to obtain a clinical applicability. In this attempt, a cannula-based electrode design was achieved by insulating the anodic diamond layer from a cathodic cannula, using a second layer of non-conducting diamond. The undoped diamond (UDD) layer was successfully grown in a spotted pattern, resulting in a perfectly insulated yet still functional BDD layer, which can operate as a miniaturized flow reactor for medical applications. The spotted pattern was achieved by introducing a partial copper layer on top of the BDD layer, which was subsequently removed after growing the undoped diamond layer via etching. The initial analytical observations showed promising results for further chemical and microbial investigations.
CRIS-Team Scopus Importer:2023-10-06
Keywords: applied electrochemistry; BDD; biocompatible diamond; boron-doped diamond; carbon insulator; diamond coating; diamond for environment; diamond for health; disinfection

Electrochemical Disinfection of Dental Implants Experimentally Contaminated with Microorganisms as a Model for Periimplantitis - Koch, Maximilian; Göltz, Maximilian; Meng, Xiangjun; Karl, Matthias; Rosiwal, Stefan; Burkovski, Andreas (Journal of Clinical Medicine, 2020)
Despite several methods having been described for disinfecting implants affected by periimplantitis, none of these are universally effective and may even alter surfaces and mechanical properties of implants. Boron-doped diamond (BDD) electrodes were fabricated from niobium wires and assembled as a single instrument for implant cleaning. Chemo-mechanical debridement and air abrasion were used as control methods. Different mono-species biofilms, formed by bacteria and yeasts, were allowed to develop in rich medium at 37 °C for three days. In addition, natural multi-species biofilms were treated. Implants were placed in silicone, polyurethane foam and bovine ribs for simulating different clinical conditions. Following treatment, the implants were rolled on blood agar plates, which were subsequently incubated at 37 °C and microbial growth was analyzed. Complete electrochemical disinfection of implant surfaces was achieved with a maximum treatment time of 20 min for Candida albicans, Candida dubliniensis, Enterococcus faecalis, Roseomonas mucosa, Staphylococcus epidermidis and Streptococcus sanguinis, while in case of spore-forming Bacillus pumilus and Bacillus subtilis, a number of colonies appeared after BDD electrode treatment indicating an incomplete disinfection. Independent of the species tested, complete disinfection was never achieved when conventional techniques were used. During treatment with BDD electrodes, only minor changes in temperature and pH value were observed. The instrument used here requires optimization so that higher charge quantities can be applied in shorter treatment times.
Keywords: air abrasion; antimicrobial treatment; biofilm; boron-doped diamond; mechanical debridement; reactive oxygen species

Influence of In-Situ Electrochemical Oxidation on Implant Surface and Colonizing Microorganisms Evaluated by Scanning Electron Microscopy - Göltz, Maximilian; Koch, Maximilian; Detsch, Rainer; Karl, Matthias; Burkovski, Andreas; Rosiwal, Stefan (Materials, 2019)
Peri-implantitis is a worldwide increasing health problem, caused by infection of tissue and bone around an implant by biofilm-forming microorganisms. Effects of peri-implantitis treatment using mechanical debridement, air particle abrasion and electrochemical disinfection on implant surface integrity were compared. Dental implants covered with bacterial biofilm were cleaned using mechanical debridement and air particle abrasion. In addition, implants were disinfected using a novel electrochemical technique based on an array of boron-doped diamond (BDD) coated electrodes. Following treatment and preparation, the implants were inspected by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Mechanical debridement led to changes in surface topography destroying the manufacturer’s medium-rough surface by scratch formation. Air particle abrasion led to accumulation of the abrasive used on the implant surface. With both treatment options, appearance of bacteria and yeasts was not affected. In contrast, electrochemical disinfection did not cause alterations of the implant surface but resulted in distorted microbial cells. Electrochemical disinfection of implant surfaces using BDD electrodes may constitute a promising treatment option for cleaning dental implant surfaces without negatively affecting materials and surface properties.
Keywords: Candida; Enterococcus; debridement; peri-implantitis; disinfection; microscopy; electron; scanning

Pilot Study on the Use of a Laser-Structured Double Diamond Electrode (DDE) for Biofilm Removal from Dental Implant Surfaces - Koch, Maximilian; Burkovski, Andreas; Zulla, Manuel; Rosiwal, Stefan; Geissdorfer, Walter; Dittmar, Roman; Grobecker-Karl, Tanja (Journal of Clinical Medicine, 2020)
No proper treatment option for peri-implantitis exists yet. Based on previous studies showing the in vitro effectiveness of electrochemical disinfection using boron-doped diamond electrodes, novel double diamond electrodes (DDE) were tested here. Using a ceramic carrier and a laser structuring process, a clinically applicable electrode array was manufactured. Roughened metal discs (n = 24) made from Ti-Zr alloy were exposed to the oral cavities of six volunteers for 24 h in order to generate biofilm. Then, biofilm removal was carried out either using plastic curettes and chlorhexidine digluconate or electrochemical disinfection. In addition, dental implants were contaminated with ex vivo multispecies biofilm and disinfected using DDE treatment. Bacterial growth and the formation of biofilm polymer were determined as outcome measures. Chemo-mechanical treatment could not eliminate bacteria from roughened surfaces, while in most cases, a massive reduction of bacteria and biofilm polymer was observed following DDE treatment. Electrochemical disinfection was charge- and time-dependent and could also not reach complete disinfection in all instances. Implant threads had no negative effect on DDE treatment. Bacteria exhibit varying resistance to electrochemical disinfection with Bacillus subtilis, Neisseria sp., Rothia mucilaginosa, Staphylococcus haemolyticus, and Streptococcus mitis surviving 5 min of DDE application at 6 V. Electrochemical disinfection is promising but requires further optimization with respect to charge quantity and application time in order to achieve disinfection without harming host tissue.
CRIS-Team WoS Importer:2020-11-06

Preclinical Testing of Boron-Doped Diamond Electrodes for Root Canal Disinfection—A Series of Preliminary Studies - Koch, Maximilian; Palarie, Victor; Koch, Lisa; Burkovski, Andreas; Zulla, Manuel; Rosiwal, Stefan; Karl, Matthias (Microorganisms, 2022)
While numerous approaches have meanwhile been described, sufficient disinfection of root canals is still challenging, mostly due to limited access and the porous structure of dentin. Instead of using different rinsing solutions and activated irrigation, the electrolysis of saline using boron-doped diamond (BDD) electrodes thereby producing reactive oxygen species may be an alternative approach. In a first step, experiments using extracted human teeth incubated with multispecies bacterial biofilm were conducted. The charge quantities required for electrochemical disinfection of root canals were determined, which were subsequently applied in an animal trial using an intraoral canine model. It could be shown that also under realistic clinical conditions, predictable disinfection of root canals could be achieved using BDD electrodes. The parameters required are in the range of 5.5 to 7.0 V and 9 to 38 mA, applied for 2.5 to 6.0 min with approximately 5 to 8 mL of saline. The direct generation of disinfective agents inside the root canal seems to be advantageous especially in situations with compromised access and limited canal sizes. The biologic effect with respect to the host reaction on BDD-mediated disinfection is yet to be examined.
CRIS-Team Scopus Importer:2022-04-22
Keywords: antimicrobial treatment; canine tooth model; electrochemical disinfection; endodontics; reactive oxygen species

Root Canal Obturation by Electrochemical Precipitation of Calcium Phosphates - Koch, Maximilian; Palarie, Victor; Göltz, Maximilian; Kurzer, Marvin; Zulla, Manuel; Rosiwal, Stefan; Willner, Marian; Burkovski, Andreas; Karl, Matthias (Applied Sciences, 2022)
Achieving adequate disinfection and preventing reinfection is the major goal in endodontic treatment. Variation in canal morphology and open porosity of dentine prevents achieving complete disinfection. Questionable biocompatibility of materials as well as a lack of sealing ability questions the usefulness of current obturation methods. With a novel disinfection approach based on the use of boron-doped diamond (BDD) electrodes having shown promising results it was the goal of this series of experiments to investigate the possibility of BDD-mediated in situ forming of a biocompatible obturation material. A combination of calcium phosphate and maleic acid was used as precursor solution while Ion Chromatography Mass Spectrometry (IC-MS), Raman spectroscopy (RAMAN), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), dye penetration and micro-computed tomography (µCT) were applied for characterizing the precipitate. It was possible to achieve a BDD-mediated precipitation of brushite in a clinically applicable timeframe. However, tight sealing of the canal system based on brushite could not be achieved.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Boron-doped diamond; Brushite; Hydroxyapatite; Obturation; Reactive oxygen species